Concrete air permeability “in situ”test: status quo - Ebensperger, Luis; Torrent, Roberto (Revista Ingeniería de Construcción, 2010)
The authors have been involved in the creation, preliminary tests and development of the “Torrent Method”, which is intended to test air permeability in concrete. It’s been more than 15 years since such foundational research and, now, this paper presents a review of the evolution and current situation of the Method, included in the Switzerland standards in 2003. Application examples conducted in laboratory and civil works (bridges, tunnels, and so on) are introduced, including data from different countries worldwide. Correlations between the air permeability coefficient kT and other durability indicators, such as chloride migration (ASTM C1202), penetration of water under pressure (EN 12390-8) or capillary action are presented. Finally the future prospective uses are discussed, as quality control tool for new structures, considering relevant implications they would lead to, as well as the diagnosis on existing structures.